A Hierarchy of Perceptual Training in Low Vision - Faubert, J; Overbury, O.; Goodrich, G.L (Canadian Journal of Optometry, 2021)
A growing concern in low vision care is whether people afflicted with a visual impairment can adapt to their condition and relearn to perform lost functional abilities. A purely sensory-physiological approach to this issue is restricted because 1) low vision patients often have below what is normally assumed as the basic necessary sensory input for many functional tasks (e.g. reading) and 2) in many cases, such an approach assumes a lack of plasticity past a critical period of acquisition. An alternative approach is that there is some useful plasticity or ability to relearn at all ages even though they may differ quantitatively and/or qualitatively.